PENERAPAN MEDIA KAHOOT!! DENGAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) SEBAGAI UPAYA MENINGKATKAN PEMAHAMAN KOGNITIF SISWA SEKOLAH DASAR - Sinta Dwi Rahayu; Ivayuni Listiani; Eka Rahayu Nurmaningsih (STKIP Subang, 2024)
The implementation of learning that applies Kahoot! learning media with the Culturally Responsive Teaching approach can improve students' cognitive understanding. The learning process implemented integrates culture and relates real material to the surrounding environment so that the understanding obtained is meaningful. The purpose of this study was to (1) describe the effect of Kahoot! learning media with the Culturally Responsive Teaching approach on students' cognitive understanding (2) improve students' cognitive learning outcomes in the Indonesian Language subject on intrinsic elements. The research method used is a qualitative descriptive method with a type of classroom action research. This study uses the Kemmis and Mc.Teggart research design with 3 learning cycles. The activities of each cycle include planning, action, observation and reflection activities. The subjects of this study were grade V students at a school in Madiun City with a total of 12 students. The object of the study was the cognitive learning outcomes of grade V students. Data collection techniques used were observation, interviews, tests and documentation. The results of this study indicate that there was a significant increase, namely in the pre-cycle of 42%, cycle 1 of 67%, cycle 2 of 75% and cycle 3 of 92%. The improvement of learning outcomes is said to be successful if 80% of students have completed the learning objective achievement criteria (KKTP) of 75. Thus, the use of Kahoot! learning media with the Culturally Responsive Teaching approach can improve the cognitive understanding of fifth grade elementary school students.